2022
DOI: 10.3389/fimmu.2022.943174
|View full text |Cite
|
Sign up to set email alerts
|

EST12 regulates Myc expression and enhances anti-mycobacterial inflammatory response via RACK1-JNK-AP1-Myc immune pathway

Abstract: c-Myc (Myc) is a well-known transcription factor that regulates many essential cellular processes. Myc has been implicated in regulating anti-mycobacterial responses. However, its precise mechanism in modulating mycobacterial immunity remains elusive. Here, we found that a secreted Rv1579c (early secreted target with molecular weight 12 kDa, named EST12) protein, encoded by virulent Mycobacterium tuberculosis (M.tb) H37Rv region of deletion (RD)3, induces early expression and late degradation of Myc protein. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The cumulative release properties of an antigen or adjuvant are key features reflecting the function of an antigen delivery system. Live-animal imaging methods are commonly used to analyze the release characteristics of fluorescently labeled antigens delivered from the injection site, and the fluorescence imaging of isolated main organs and tissues can represent the in vivo biodistribution of fluorescently labeled NPs at different time points ( 51 ). In the current experiment, the fluorescence intensity of DiD-stained CS-gp90@M-M and CS-gp90@M NPs at the injection site was obvious at 12 h and then decreased gradually over time.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative release properties of an antigen or adjuvant are key features reflecting the function of an antigen delivery system. Live-animal imaging methods are commonly used to analyze the release characteristics of fluorescently labeled antigens delivered from the injection site, and the fluorescence imaging of isolated main organs and tissues can represent the in vivo biodistribution of fluorescently labeled NPs at different time points ( 51 ). In the current experiment, the fluorescence intensity of DiD-stained CS-gp90@M-M and CS-gp90@M NPs at the injection site was obvious at 12 h and then decreased gradually over time.…”
Section: Discussionmentioning
confidence: 99%
“…The TNF signaling pathway is vital to restricting Mtb growth, and interactions between Mtb growing under hypoxia and host macrophages can induce the activation of the TNF signaling pathway, the DNA damage stress response, and apoptosis ( Zhang et al., 2020 ). It has been reported that the JAK-STAT pathway contributes to the expression of multiple pro-inflammatory cytokines to clear Mtb ( Zhong et al., 2017 ; Wu et al., 2022 ). IL-17 is secreted by Th17 cells, a subset of CD4 + T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis activation also involves the gasdermin (GSDM) family and several canonical and non-canonical inflammasome-induced pathways (caspases-1/3/6/7/ GSDMB, caspase-8/GSDMC, caspase-8/GSDMD, and caspase-3/ GSEME). Recently, Mtb effector EST12-induced pyroptosis activated the RACK1/NLRP3/caspase-1/GSDMD or RACK1-JNK-AP1-Myc signaling pathways to enhance the anti-mycobacterial inflammatory response (Qu et al, 2020;Wu et al, 2022). However, the precise molecular mechanisms that cause pyroptosis during TB remain enigmatic.…”
Section: Pyroptosismentioning
confidence: 99%